Perception of mentoring behaviours among USM medical students - Mohammad, Jamilah Al-Muhammady (2016)
INTRODUCTION: Educators around the globe have agreed that effective mentoring relationships have been proven to promote personal and professional growth of future doctors. These relationships are affected by multiple factors. Unfortunately, there is lacking of evidence to support the effectiveness of mentoring practice in USM medical school. From that notion, this study aimed to evaluate the mentoring behaviours of mentors in USM medical school. METHODOLOGY: A cross-sectional study was conducted on 632 second to fifth year medical students. The mentoring behaviours were measured by the Mentor Behavior Scale (MBS) and rated by the medical students. The MBS measures four aspects of mentoring behaviour that include mentoring relationship structure, engagement, autonomy support and competency support. Each aspect was interpreted as positive areas, room for improvements, and areas of concern. Data analysis was performed by SPSS version 22. RESULTS: A total of 508 (80.4%) respondents participated in the study. The global supportive mentoring behaviour was perceived as areas for improvements as indicated by mean score of in between 45 – 59. The mentoring relationship structure [Mean (SD) = 28.44 (7.46)], engagement [Mean (SD) = 6.76 (2.12)], and competency support [Mean (SD) = 10.51 (3.10)] were perceived as areas for improvement as well. The autonomy support [Mean (SD) = 5.85 (1.68)] was perceived as an area of concern. Race, mode of mentor selection, year of study, frequency of meeting and duration of meeting significantly affecting the mentoring behaviours. Mentoring behaviours were not associated with gender and entry qualification. CONCLUSION: The mentoring behaviours of mentors in USM medical school were perceived by students as acceptable yet there were rooms for improvements. However, further inspection is required to explore reasons for low perception towards the autonomy support. In addition, several factors should be considered to enhance the quality of mentoring system in the medical school.